Raman light scattering for systems with strong short-range interaction - Stasyuk, I.V.; Mysakovych, T.S. (Condensed Matter Physics, 2000)
Various type contributions to Raman light scattering are investigated for the Hubbard, t − J and pseudospin-electron models. To construct the polarizability operator the microscopic approach is used, which is based on the operator expansion in the terms of the Hubbard operators using t and J as formal parameters of the expansion. Two different contributions to the dipole momentum are taken into account: one is connected with the nonhomeopolarity of ﬁlling of the electron states on a site, another – with the dipole transitions from the ground state to the excited ones (for the case of the Hubbard model) and with the dipole momentum of the pseudospins (for the case of the pseudospin- electron model). The general expressions for the scattering tensor components describing the magnon, electron (intraand interband) and pseudospin scattering are obtained. The resonant and nonresonant contributions are separated; their role at the change of the hole concentration due to doping is studied. The dependence of the Raman scattering tensor on the polarization of the incident and scattered light is investigated.